Extension of antiaromatic norcorrole by cycloaddition. Issue 20 (20th February 2018) - Fu, Xinliang; Meng, Yankui; Li, Xiaofang; Stępień, Marcin; Chmielewski, Piotr J.
Abstract : Cycloaddition of iminonitrile to norcorrolatonickel(ii ) yields the first chiral antiaromatic tetrapyrrole and pyrazole-fused system of enhanced paratropicity. Abstract : The antiaromatic ring of norcorrole, a contracted tetrapyrrolic porphyrinoid, was subjected to [2+3] dipolar cycloaddition of iminonitriles. The paratropic character of the resulting chiral chlorins was retained. The chlorins were easily dehydrogenated in the presence of air, yielding pyrazole-fused norcorroles with markedly enhanced paratropicity.